Attractiveness of cowpea genotypes for Bemisia tabaci B‑biotype oviposition - Cruz, Patrícia Leite; Baldin, Edson Luiz Lopes; de Castro, Maria de Jesus Passos; Fanela, Thiago Luis Martins; da Silva, Paulo Henrique Soares (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to evaluate the attractiveness of cowpea genotypes for Bemisia tabaci B‑biotype oviposition, and to identify possible sources of resistance. Fifty‑one genotypes were evaluated using free‑choice tests. The genotypes were randomly divided into two groups, using the genotype Canapu as a susceptible control. The fourteen most promising genotypes (seven from each group) were selected for complementary testing (with or without choice). In the free‑choice test, BRS‑Urubuquara, TVU‑36, TE93‑244‑23 F‑1, BR 17‑Gurgueia, BRS‑Marataoã, MNC99‑541 F‑21, and TE97‑304 G‑4 were less attractive to the whitefly. The genotypes TE93‑244‑23 F‑1 and TVU‑36 stud out and showed non‑preference resistance for ovoposition. In the no‑choice test, the genotype TVU‑36 showed resistance by this same mechanism.